INVESTIGATING THE IMPACT OF MATERIAL FATIGUE ON STRUCTURAL IN HIGH-PERFORMANCE MECHANICAL SYSTEMS - Muhammad Aqeel; Asad Ali; Zhao Xianrui; Zhao Hong Quan; Mohsin Riaz (Spectrum of Engineering Sciences, 2025)
Background: The structural integrity and operational reliability of high-performance mechanical systems are substantially impacted by material fatigue. This knowledge is vital for improving and prolonging the performance and lifespan of systems that face fatigue failures, especially as demands for a higher level of safety and durability are being placed on many engineering applications. Severe fatigue failure prediction and prevention have been extensively studied, yet accurately predicting fatigue life and establishing effective prevention methods remain challenging. Objective: This study aims to analyze the primary causes of material fatigue, evaluate existing mitigation techniques, and explore the potential of emerging technologies in enhancing fatigue resistance. Methods: A systematic survey was conducted among 135 professionals in the mechanical systems engineering field, including engineers, scientists, researchers, and technicians with diverse expertise levels. The survey investigated industry trends, key contributions, and perspectives on material fatigue mitigation. Additionally, a literature review was performed to analyze recent advances in material science and fatigue prediction models to contextualize the findings within the broader research landscape. Key Findings: Repetitive loading conditions were identified as the primary contributor to material fatigue, as reported by 75% of respondents. Environmental effects were another significant factor, with 60% of respondents acknowledging their impact on material degradation. More than two-thirds (67%) of respondents had encountered structural failures due to fatigue in their professional experience. Preventive strategies such as regular inspections and high-quality materials were found to have only moderate effectiveness. Smart monitoring systems and computational fatigue models showed great potential but faced challenges related to technological constraints and cost. Conclusion: To address material fatigue challenges in mechanical systems, improved predictive maintenance strategies and the development of novel materials are essential. Future research should focus on developing fatigue-resistant alloys, self-healing materials, and AI-driven monitoring systems to enhance structural durability. Computational modeling and real-time data analytics will play a critical role in understanding fatigue progression and defining future engineering solutions, ultimately elevating industry standards.